CUSTOMER RELATIONSHIP MANAGEMENT DAN PERFORMANSI PELABUHAN - Triyani, Devi; Lasse, David Aroschi; Widodo, Widodo; Hasan, Husni (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2017)
The research objective is to determine the impact of relationship management with land transportation service providers to the performance of the port with a mediation service that adds value to the PT. Indonesia Vehicle Terminal (IKT), Tanjung Priok, Jakarta. The study uses a quantitative approach to associative and the data processed by the program LISREL 8.8. The sample was 100 of service users with quota sampling technique. Data analysis was conducted using descriptive and inferential statistical path analysis. The results show: relationship management with providers of land transportation services have a direct positive impact and significant to the performance of the port, services that provide added value affect prositive direct impact and significant to the performance of the port, the relationship management with providers of land transportation services have a positive direct impact and significant to the service that provides value added, and the relationship management with providers of land transportation services have positive indirect impact and significant to the performance of the port with a mediation service that adds value. The conclusion is relationship management with providers of land transportation services has an impact on the performance of the port with a mediation service that adds value, therefore performance can be improved through the port relationship management with providers of land transportation services and services that provide added value.